2022
DOI: 10.1038/s41598-022-21774-4
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic analysis and optimal control considering cross transmission and variation of information

Abstract: Cross-transmission of information has a profound influence on the progress of science and technology and the discipline integration in the field of education. In this work, knowledge gained from the viral recombination and variation in COVID-19 transmission is applied to information transmission. Virus recombination and virus variation are similar to the crossing and information fusion phenomena in information transmission. An S2I4MR model with information crossing and variation is constructed. Then, the local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…From system (3), the only solution on Ω that satisfies L P* ′(t) 0 is P*. Based on the LaSalle invariance principle [46], it can be demonstrated that the globally asymptotically stable equilibrium point P* of uncertain information propagation exists in the feasible domain Ω when R 0 > 1 holds, which proves Theorem 4.…”
Section: Stability Analysis Of Equilibrium Pointsmentioning
confidence: 59%
See 1 more Smart Citation
“…From system (3), the only solution on Ω that satisfies L P* ′(t) 0 is P*. Based on the LaSalle invariance principle [46], it can be demonstrated that the globally asymptotically stable equilibrium point P* of uncertain information propagation exists in the feasible domain Ω when R 0 > 1 holds, which proves Theorem 4.…”
Section: Stability Analysis Of Equilibrium Pointsmentioning
confidence: 59%
“…However, in reality, some Internet users choose to clarify uncertain information when faced with it, while others maintain their behavior after contacting other Internet users. In a previous study [46], observed this effect but did not consider that some netizens may not immediately change their minds after interacting with others, but rather become more thoughtful.…”
Section: Comparison With Existing Research On Uncertain Information D...mentioning
confidence: 87%